C24 Ceramide Lipid Nanoparticles for Skin Wound Healing - Lee, Ji Hye; Kim, Jin Hyun; Hyeon, Tong Il; Min, Khee Tae; Lee, Se Young; Ko, Han Chul; Choi, Hong Seok; Ju, Kuk Youn; Cho, Young Seok; Yoon, Tae Jong (Pharmaceutics, 2025)
Background/Objectives: C24 ceramide plays a crucial role in skin regeneration and wound healing; however, its hydrophobic nature limits its application in therapeutic formulations. This study aims to enhance the bioavailability and efficacy of C24 ceramide by developing ceramide-based lipid nanoparticles (C24-LNP) and evaluate their impact on skin regeneration and wound healing. Methods: C24-LNP was synthesized and characterized for aqueous stability and bioavailability. In vitro experiments were conducted to assess its effects on keratinocyte proliferation and migration. Molecular biological analysis examined key signaling pathways, including AKT and ERK1/2 phosphorylation. Additionally, an in vivo mouse wound model was utilized to evaluate wound healing efficacy, with histological analysis performed to assess epidermal and dermal regeneration. Results: C24-LNP exhibited improved aqueous stability and bioavailability compared to free C24 ceramide. In vitro studies demonstrated that C24-LNP significantly promoted keratinocyte proliferation and migration. Molecular analysis revealed activation of the AKT and ERK1/2 signaling pathways, which are critical for cell growth and skin regeneration. In vivo wound healing experiments showed that C24-LNP accelerated wound closure compared to the control group. Histological analysis confirmed enhanced epidermal and dermal regeneration, leading to improved structural and functional skin repair. Conclusion: The lipid nanoparticle formulation of C24 ceramide effectively increases its bioavailability and enhances its therapeutic efficacy in skin regeneration and wound healing. C24-LNP presents a scalable and cost-effective alternative to traditional growth factor-based therapies, offering significant potential for clinical applications in wound care and dermatological treatments.
Keywords: C24 ceramide; collagen regeneration; lipid nanoparticle; re-epithelialization; wound healing